Customs Intelligence And Risk Management In Sustainable Supply Chain For General Customs Department Logistics - Omar M. Shubailat; Murad Ali Ahmad Al-Zaqeba; Aziz Madi; Ahmad Moh’D Ababneh (growingscience, 2024)
Indexed by Scopus